Aligning sustainability and corporate strategies: the case of hybrid-electric vehicles and Fiat-Chrysler Automobiles - Narullo, Andrea (2015)
This study analyses the integration of environmental sustainability into corporate strategy in the context of the car industry. The implementation of sustainability strategies and the development of hybrid-electric vehicles are investigated with reference to the case of a major player in the industry. Among the applications of electric mobility, which will increase the market presence in the forthcoming years due to stringent regulations and customer preferences, the research focused on hybrid-electric vehicles. The sustainability strategies of major car manufacturers and the subsequent implications in terms of product development, with a particular attention to hybrid-electric vehicles, were analysed via secondary data. Additionally, primary data was collected about the sustainability strategy of a major player in the industry and used to perform a case study. The analysis focused on critical drivers and aspects that impact on sustainability strategies aimed at reducing the environmental footprint of the car industry and on the development of hybrid vehicles. The analysis of the data showed that Fiat-Chrysler Automobiles (FCA) had a minor emphasis on electric mobility in terms of sustainability reporting. The conclusion presents an assessment of FCA’s corporate strategy in terms of environmental sustainability and a framework for HEV development with four different approaches that impact on the sustainability strategy of a carmaker.